(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The acquisition of state independence by the Republic of Uzbekistan marked the beginning of a new stage in the country’s social and economic development. Since then, extensive reforms have been implemented in all spheres of life to establish a democratic state governed by the rule of law and a market-based economy. Within this transformation, non-governmental non-profit organizations (NGOs) have emerged as a key element of civil society. They play an important role in protecting human rights, providing social services, promoting public awareness, and strengthening the partnership between the state and society.